A Study On A Velogenic Viscerotropic Newscastle Disease Virus In Vitro And In Vivo - Lai, Chooi May (1985)
The velogenic viscerotropic Newcastle disease virus or the Asiatic strain has been considered the most virulent strain of Newcastle disease virus. It is commonly found in Southeast Asia and it has been known to cause 100\ mortality in susceptible flocks. In spite of this, very little research has been conducted on it as many countries prohibit the handling of this strain of virus. In view of this, a project has been undertaken at Universiti Pertanian Malaysia to study the biological properties, cytopathogenicity and morphogenesis of a locally isolated velogenic viscerotropic Newcastle disease virus and to determine its effects on the trachea of nonvaccinated and vaccinated chickens. The in vitro study has shown that this virus has a mean death time of 66 hours, and an intracerebral pathogenicity index of 1.90 . Polykaryocytosis is the principal form of cytopathic effect it produces in chick embryo fibroblasts and cells infected by it haemadsorp red blood cells. This virus plaques in cell culture. Negatively stained virus particles have diameters ranging from 100 to 600 nanometers. Electron microscopy demonstrated that the virus replicates in the cytoplasm of infected cells and aggregates of nucleocapsids are found in the cytoplasm. The virus matures at the cell membrane and is released by budding.